2019
DOI: 10.1039/c9cy00744j
|View full text |Cite
|
Sign up to set email alerts
|

Deactivation mechanism of hydrotalcite-derived Ni–AlOx catalysts during low-temperature CO2 methanation via Ni-hydroxide formation and the role of Fe in limiting this effect

Abstract: Ni–Fe/AlOx with nanosheet structure, enhance the reducibility and stability of the Ni-hydroxide during the catalytic reaction due to the formation of spinel phase which stabilize smaller Ni nanoparticle with a weaker interaction with the support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 58 publications
2
23
0
3
Order By: Relevance
“…Consequently, the catalyst with this specific ratio offered the best low-temperature catalytic performance in terms of CO2 conversion and CH4 selectivity, whereas catalysts with higher Fe contents experienced a significant drop for these values (Figure 4). Mebrahtu et al [50] also indicated a possible deactivation pathway for monometallic Ni Mebrahtu et al [39] used hydrotalcite-precursors with a tailored Fe/Ni ratio in order to prepare NiFe/(Mg,Al)O x catalysts with high levels of metal intermixing and dispersion. The Fe/Ni ratio played a crucial role in the physicochemical properties and the catalytic performance of the prepared catalysts.…”
Section: Promotion With Fementioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, the catalyst with this specific ratio offered the best low-temperature catalytic performance in terms of CO2 conversion and CH4 selectivity, whereas catalysts with higher Fe contents experienced a significant drop for these values (Figure 4). Mebrahtu et al [50] also indicated a possible deactivation pathway for monometallic Ni Mebrahtu et al [39] used hydrotalcite-precursors with a tailored Fe/Ni ratio in order to prepare NiFe/(Mg,Al)O x catalysts with high levels of metal intermixing and dispersion. The Fe/Ni ratio played a crucial role in the physicochemical properties and the catalytic performance of the prepared catalysts.…”
Section: Promotion With Fementioning
confidence: 99%
“…Consequently, the catalyst with this specific ratio offered the best low-temperature catalytic performance in terms of CO 2 conversion and CH 4 selectivity, whereas catalysts with higher Fe contents experienced a significant drop for these values ( Figure 4 ). Mebrahtu et al [ 50 ] also indicated a possible deactivation pathway for monometallic Ni catalysts via the formation of Ni hydroxides caused by the water produced in situ upon methanation. It was found that the introduction of Fe prevented the formation of Ni-OH species, thus increasing the catalytic activity of such systems.…”
Section: Promotion With Transition Metalsmentioning
confidence: 99%
See 1 more Smart Citation
“…20 Active state of the Ni-Fe catalyst under steady state conditions A comparison of the catalytic activity of Ni and Ni-Fe catalysts including detailed structural information about monometallic Ni catalysts during CO 2 methanation is given in other studies. 23,29,30,63,64 Hence, the focus in this study is on gaining information about structural composition of the Ni-Fe catalyst with operando techniques. The Ni-Fe/γ-Al 2 O 3 catalyst was already active at 250°C, providing a CO 2 conversion of 5% (Table 1) and a selectivity to methane of 75%.…”
Section: Catalyst Activation and Ni-fe Alloy Formationmentioning
confidence: 99%
“…Fe x C as additional active sites, 28 enhanced but limited CO 2 dissociation on Fe 2+ under irreversible formation of Fe 3+ , 28 or protection of the active Ni 0 centers by iron. 21,30 Recently, Burger et al suggested via ex situ studies that segregation of Fe to the particle surface under formation of Fe 2+ might provide redox active sites for enhanced CO 2 activation. 29 In conclusion, the detailed role of iron in bimetallic Ni-Fe catalysts during CO 2 methanation remains unclear and requires monitoring of the structure of iron under reaction conditions.…”
Section: Introductionmentioning
confidence: 99%